Specific quantitative detection of Streptococcus suis and Actinobacillus pleuropneumoniae in co-infection and mixed biofilms - Yi, Li; Jin, Manyu; Gao, Mengxia; Wang, Haikun; Fan, Qingying; Grenier, Daniel; Sun, Liyun; Wang, Shaohui; Wang, Yang (Frontiers in Cellular and Infection Microbiology, 2022)
Respiratory infections seriously affect the swine industry worldwide. Co-infections of two vital pathogenic bacteria Streptococcus suis (S. suis) and Actinobacillus pleuropneumoniae (A. pleuropneumoniae), colonizing the respiratory tract often occurs in veterinary clinical practice. Moreover, our previous research found that S. suis and A. pleuropneumoniae can form biofilm in vitro. The formation of a mixed biofilm not only causes persistent infections, but also increases the multiple drug resistance of bacteria, which brings difficulties to disease prevention and control. However, the methods for detecting S. suis and A. pleuropneumoniae in co-infection and biofilm are immature. Therefore, in this study, primers and probes were designed based on the conservative sequence of S. suis gdh gene and A. pleuropneumoniae apxIVA gene. Then, a TaqMan duplex real-time PCR method for simultaneous detection of S. suis and A. pleuropneumoniae was successfully established via optimizing the reaction system and conditions. The specificity analysis results showed that this TaqMan real-time PCR method had strong specificity and high reliability. The sensitivity test results showed that the minimum detection concentration of S. suis and A. pleuropneumoniae recombinant plasmid was 10 copies/μL, which is 100 times more sensitive than conventional PCR methods. The amplification efficiencies of S. suis and A. pleuropneumoniae were 95.9% and 104.4% with R2 value greater than 0.995, respectively. The slopes of the calibration curves of absolute cell abundance of S. suis and A. pleuropneumoniae were 1.02 and 1.09, respectively. The assays were applied to cultivated mixed biofilms and approximately 108 CFUs per biofilm were quantified when 108 CFUs planktonic bacteria of either S. suis or A. pleuropneumoniae were added to biofilms. In summary, this study developed a TaqMan real-time PCR assay for specific, accurate quantification of S. suis or A. pleuropneumoniae in mixed biofilms, which may help for the detection, prevention and control of diseases caused by a bacterial mixed infection involving S. suis and A. pleuropneumoniae.